2009
DOI: 10.1136/thx.2008.111237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather factors on Mycoplasma pneumoniae pneumonia

Abstract: Background: Although multiple combinations of weather factors may contribute to an increased incidence of Mycoplasma pneumoniae pneumonia, few studies have investigated the association between weather factors and cases of M pneumoniae pneumonia. Methods: Data on cases of M pneumoniae pneumonia and weather factors in Fukuoka, Japan from 1999 to 2007 were obtained and time-series analysis was used to assess the effects of weather variables on M pneumoniae pneumonia cases, adjusting for confounding factors. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 38 publications
5
44
2
1
Order By: Relevance
“…During the entire period, the changes in the annual cycle of positive rates were irregular, with peaks in early summer (in 2012), mid-summer (in 2013), and early autumn (in 2014). This is in line with reports describing more M. pneumoniae infections with increased relative humidity and ambient temperature (19,20). In our neighborhood areas, recent epidemic outbreaks of M. pneumoniae infections were also noted in South Korea from 2010 to 2011, in Japan from 2011 to 2012, and in Beijing and Shanghai, China, in 2012 (4,21,22).…”
Section: Discussionsupporting
confidence: 78%
“…During the entire period, the changes in the annual cycle of positive rates were irregular, with peaks in early summer (in 2012), mid-summer (in 2013), and early autumn (in 2014). This is in line with reports describing more M. pneumoniae infections with increased relative humidity and ambient temperature (19,20). In our neighborhood areas, recent epidemic outbreaks of M. pneumoniae infections were also noted in South Korea from 2010 to 2011, in Japan from 2011 to 2012, and in Beijing and Shanghai, China, in 2012 (4,21,22).…”
Section: Discussionsupporting
confidence: 78%
“…[21] The effects of temperature were such that irrespective of relative humidity, an increase in temperature resulted in a decreased airborne survival time in laboratory settings. [21] In real-life, Onozuka et al [8] found the number of cases of MPP increased with higher temperature or relative humidity in the weeks preceding disease onset which was opposite to the experimental results. Although humidity was thought to be an important factor for survival of M. pneumoniae, [8,21] our data proved no correlation between MPP rate and humidity or between temperature and humidity.…”
Section: Discussioncontrasting
confidence: 47%
“…[21] In real-life, Onozuka et al [8] found the number of cases of MPP increased with higher temperature or relative humidity in the weeks preceding disease onset which was opposite to the experimental results. Although humidity was thought to be an important factor for survival of M. pneumoniae, [8,21] our data proved no correlation between MPP rate and humidity or between temperature and humidity. Nor other meteorological factors including monthly mean precipitation and raining days were found to be correlated to the MPP rate.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although several low humidity studies were obtained during the literature search, many studies focused on pneumonia in humid environments (Onozuka et al, 2009;Negrisoli and Nascimento, 2013;Ramos, 2013). In laboratory tests, four studies considered aerosol viability (Dunklin and Puck, 1948;Wright et al, 1968;Theunissen et al, 1993;Ko et al, 2000) and one study examined the spread of pathogens on fomites (Lopez et al, 2013), with conditions shown in Figure 3.…”
Section: Bacteriamentioning
confidence: 99%